Crystal structure of pyridinium tetrakis[1,1,1-trifluoro-2,4-pentadionato-K2 O,O′]lutetium(III) C20F12H16LuO8C5H6N - Wang Yan; Wang Jianming (Zeitschrift für Kristallographie - New Crystal Structures, 2025)
C25H22F12LuNO8, monoclinic, P21/c, a = 10.4573(2) Å, b = 19.4072(3) Å, c = 15.7199(2) Å, β = 103.842(2)°, V = 3097.66(9) Å3, Z = 4, R gt(F) = 0.0912, wRref (F 2) = 0.0921, T = 150 K.